STRATEGY OF AGRO TOURISM DEVELOPMENT IN GOMBENGSARI DISTRICT BANYUWANGI - Astutik, Ninik Puji (Institut Pariwisata dan Bisnis Internasional, 2017)
The purpose of this research is to find out agro-tourism development strategy of Gombengsari based on SWOT analysis result. By determining External Factor Analysis Summary (EFAS) and Internal Factor Analysis Summary (IFAS). While the key variables of this research discussion is the Marketing Mix that consists of product, price, place, and promotion. The results of research coffee plantations and cultures that deserve to be a tourist attraction with affordable pricing that is managed by the local community by forming a group of tourism awareness and use of internet media as a means to market tourism. Gombengsari agro-tourism development strategy that is; 1) To develop tourism product; 2) Socialization to the society; 3) Infrastructure development; 4) Tourism product differsivication; 5) To develop the agro tourism marketing; 6) Human resources development; 7) To develop an operational team.